Analisis Tantangan Dan Pengelolaan Risiko Proyek Pembangunan Ibu Kota Nusantara Dengan Pendekatan Kualitatif: Analysis Of Challenges And Risk Management Of The Archipelago Capital City Development Project With A Qualitative Approach - Dewi, Rafama; Soemardi, Biemo Woerjanto; Waty, Mega (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The Nusantara Capital City (IKN) development project is one of the strategic megaprojects in Indonesia with the aim of moving the center of government to East Kalimantan. The megaproject faces a number of significant challenges, including delays in physical progress, budget constraints, constraints in land acquisition, and complex technical risks. This study aims to analyze the challenges and risk mitigation strategies implemented in the IKN project through a qualitative approach based on progress reports until September 2024. With thematic analysis using the NVivo tool, three main themes in risk mitigation were found, namely flexible financial management, the use of Building Information Modeling (BIM) technology, and a cross-sector collaborative approach. The use of BIM has proven to be effective in detecting design clash detection, which reduces technical risks in the field. In addition, the involvement of local governments and local communities in the land acquisition process accelerates negotiations and reduces the potential for social conflict. The results of this study show that cross-sector collaboration, technology integration, and adaptive budget management play an important role in ensuring the smooth running of large-scale projects. This study is expected to contribute to the development of risk management strategies in Indonesian infrastructure projects.